2012
DOI: 10.1371/journal.pone.0050009
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Analysis of Interaction and Localization of Arabidopsis SKP1-LIKE (ASK) and F-Box (FBX) Proteins

Abstract: F-Box (FBX) proteins are encoded by a multigene family present in major lineages of eukaryotes. A number of FBX proteins are shown to be subunits of SCF complex, a type of E3 ligases composed of SKP1, CULLIN, FBX and RBX1 proteins. The Arabidopsis SKP-LIKE (ASK) proteins are also members of a family and some of them interact with FBX proteins directly. To clarify how FBX and ASK proteins combine, we carried out a large-scale interaction analysis between FBX and ASK proteins using yeast two-hybrid assay (Y2H) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
62
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(64 citation statements)
references
References 28 publications
(44 reference statements)
2
62
0
Order By: Relevance
“…33 Our data confirmed these observations, showing expression of the F-box gene in all plant organs and tissues consisting of actively dividing cells, and during the stages of somatic embryogenesis, thus supporting the role of F-box in the growth and development of the three studied model plants (Figures 1-3). In L. japonicas transcriptional reporter lines, F-box expression was detected in the nodule vasculature ( Figure 2C), but was not observed in the nodules of M. truncatula.…”
Section: Discussionsupporting
confidence: 88%
“…33 Our data confirmed these observations, showing expression of the F-box gene in all plant organs and tissues consisting of actively dividing cells, and during the stages of somatic embryogenesis, thus supporting the role of F-box in the growth and development of the three studied model plants (Figures 1-3). In L. japonicas transcriptional reporter lines, F-box expression was detected in the nodule vasculature ( Figure 2C), but was not observed in the nodules of M. truncatula.…”
Section: Discussionsupporting
confidence: 88%
“…Similar to ASK1 and ASK2 in Arabidopsis and OSK1 and OSK20 in rice, SSK1 and SSK2 are broadly expressed in different tissues and their gene products, SSK1 and SSK2, were found to interact with most of the F-box proteins tested here [31,32,36,37]. In addition, phylogenetic analysis indicated that SSK1 and SSK2 were most closely related to ASK1 and ASK2 evolutionarily.…”
Section: Discussionmentioning
confidence: 83%
“…Yeasts and humans have a single SKP1 gene, while Drosophila, C. elegans contains 7 and 21 SKP1 homologues, respectively [26,29]. In plants, SKP1-like genes have also been identified in several species, including Arabidopsis, rice, wheat and citrus [30][31][32][33][34]. There are 21 putative SKP1 homologues in Arabidopsis genome, denoted as ASK for Arabidopsis SKP1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our polymorphism and transcriptome analyses of this superfamily within Arabidopsis further support this scenario with strong evidence that only a subset (∼21%) of FBX loci (mostly Common/High Exp) are under more stringent functional constraints and actively expressed. Notably, the predicted active FBX loci include those known to control important phenotypic responses in Arabidopsis and other species (12) and/or to bind SKP1 (11,30). Most of the remaining FBX loci are under more relaxed selection and, as for pseudogenes, are often expressed at basal levels.…”
Section: Discussionmentioning
confidence: 99%